Growth and economic development : essays in honour of A.P. Thirlwall - Arestis, Philip; McCombie, J. S. L.; Vickerman, R. W.; Thirlwall, A. P. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
Bearing testimony to AP Thirlwall's substantial contribution to economics over the years, this book demonstrates the considerable influence that his work on economic theory has had on his contemporaries, and the profession as a whole. It covers a range of topics including 'Thirlwall's Law', endogenous growth theory, and others.
Includes bibliographical references and index.
ijb 07/02/2019
Loans
Keywords: Economic development; Development economics